Effect of exercise therapy on adolescent idiopathic scoliosis in mild to moderate: a systematic review and network meta-analysis - Zhu, Hongfang; Li, Chengjun; Tian, Zhibo; Zhang, Qiang (Frontiers in Medicine, 2025)
ObjectivesThis study aimed to identify the most effective exercise for reducing the Cobb angle and the angle of trunk rotation (ATR) and improving the quality of life (QoL) in adolescents with idiopathic scoliosis (AIS).MethodsA systematic search of EMBASE, Web of Science, PubMed, Cochrane Library, and MEDLINE identified randomized controlled trials (RCTs) on exercise interventions for light to moderate AIS. Eligible studies involved AIS patients receiving exercise therapy, with outcomes measured by the Cobb angle, ATR, and quality of life scores. The search included articles published from the inception of these databases until June 2025. Two independent researchers conducted screening, data extraction, and quality assessment using the Cochrane risk of bias tool. Network meta-analysis (NMA) was performed using Stata 16.0 and reported per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA)-NMA guidelines. The protocol was registered in the International Prospective Register of Systematic Review (PROSPERO) (CRD42024557874).ResultsA total of 16 RCTs involving 600 participants were included in the study. Compared to controls, Schroth exercise significantly improved the Cobb angle [SMD = -1.42, 95% CI (−2.03, −0.80)] and ATR [SMD = -1.86, 95% CI (−3.05, −0.68)]. The Lyon method showed the most significant improvement in quality of life [SMD = 2.64, 95% CI (0.80, 4.49)]. The Scientific Exercises Approach to Scoliosis (SEAS) exercise also helps improve the Cobb angle, but its effect is weaker.ConclusionExercise therapy effectively reduces spinal curvature and enhances the quality of life in adolescents with AIS. Schroth exercises are most effective for improving the Cobb angle and ATR, while the Lyon therapy significantly benefits quality of life. However, due to small sample sizes, substantial between-study heterogeneity, and risk of bias, the overall certainty of evidence is low; the results should be interpreted cautiously.Systematic review registrationPROSPERO (CRD42024557874), https://www.crd.york.ac.uk/PROSPERO/view/CRD42024557874.